Study on geoheritage and water quality of Pos Hendrop hot spring, Lojing Highlands, Kelantan, Malaysia - Dony Adriansyah Nazaruddin; Zurfarahin Zulkarnain; Nur Syazwani Md. Fadilah; Mohammad Muqtada Ali Khan; Arham Muchtar Achmad Nahar (Universiti Malaysia Kelantan, 2015)
Pos Hendrop hot spring is one of the hot springs in Lojing Highlands, in the state of Kelantan, Malaysia. The hot spring is located within the Main Range Granite and is among the hottest hot spring in Malaysia. The aim of this paper is to discuss geoheritage potentials and water quality of this hot spring. Desk study was carried out by reviewing some literatures related to the topic and the study area. Field works were organized in January and August 2014 to collect data, samples, and photographs. This site has geoheritage values such as scientific, aesthetic, recreational, functional, and economic values. The in-situ water quality analysis which was conducted in 2014 during the dry and rainy seasons in Kelantan (January and August 2014) generally shows that the water quality in the measurement points of the hot spring area ranges from “Class IIB” to “Class V” based on the Interim National Water Quality Standard (INWQS) for Malaysia. This hot spring also shows a good potential to attract the interests of geoscientists and general public to visit the area. Some specific tourism and recreational activities can be done in the site such as eggs boiling, bathing and heating, hot spring therapy, and skin treatment. It is recommended that this hot spring should be conserved and developed properly as a potential geoheritage site and for a sustainable geotourism development in Lojing Highlands.